Aberrant Functional Connectivity in the Default Mode and Central Executive Networks in Subjects with Schizophrenia – A Whole-Brain Resting-State ICA Study - Littow, Harri; Huossa, Ville; Karjalainen, Sami; Jääskeläinen, Erika; Haapea, Marianne; Miettunen, Jouko; Tervonen, Osmo; Isohanni, Matti; Nikkinen, Juha; Veijola, Juha; Murray, Graham; Kiviniemi, Vesa J. (Frontiers in Psychiatry, 2015)
Neurophysiological changes of schizophrenia are currently linked to disturbances in connectivity between functional brain networks. Functional magnetic resonance imaging (fMRI) studies on schizophrenia have focused on a few selected networks. Also previously it has not been possible to discern whether the functional alterations in schizophrenia originate from spatial shifting or amplitude alterations of functional connectivity. In this study we aim to discern the differences in schizophrenia patients with respect to spatial shifting vs. signal amplitude changes in functional connectivity in the whole brain connectome. We used high model order independent component analysis (ICA) to study some 40 resting state networks (RSN) covering the whole cortex. Group differences were analysed with dual regression coupled with y-concat correction for multiple comparisons. We investigated the RSN’s with and without variance normalization in order to discern spatial shifting from signal amplitude changes in 43 schizophrenia patients and matched controls from the Northern Finland 1966 Birth Cohort. Voxel level correction for multiple comparisons revealed 18 RSN’s with altered functional connectivity, six of which had both spatial and signal amplitude changes. After adding the multiple comparison y-concat correction to the analysis for including the 40 RSN’s as well, we found that four RSN’s showed still changes. These robust changes actually seem encompass parcellations of the default mode network (DMN) and central executive networks (CEN). These networks both have spatially shifted connectivity and abnormal signal amplitudes. Interestingly the networks seem to mix their functional representations in areas like left caudate nucleus and dorsolateral pre-frontal cortex. These changes overlapped with areas that have been related to do paminergic alterations in patients with schizophrenia compared to controls.